The Kidney–Gut Axis as a Novel Target for Nutritional Intervention to Counteract Chronic Kidney Disease Progression - Sandra Cabała; Małgorzata Ożgo; Agnieszka Herosimczyk (Metabolites, 2024)
A well-balanced diet is integral for overall health, aiding in managing key risk factors for kidney damage like hypertension while supplying necessary precursors for metabolite production. Dietary choices directly influence the composition and metabolic patterns of the gut microbiota, showing promise as therapeutic tools for addressing various health conditions, including chronic kidney diseases (CKD). CKD pathogenesis involves a decline in the glomerular filtration rate and the retention of nitrogen waste, fostering gut dysbiosis and the excessive production of bacterial metabolites. These metabolites act as uremic toxins, contributing to inflammation, oxidative stress, and tissue remodeling in the kidneys. Dietary interventions hold significance in reducing oxidative stress and inflammation, potentially slowing CKD progression. Functional ingredients, nutrients, and nephroprotective phytoconstituents could modulate inflammatory pathways or impact the gut mucosa. The “gut–kidney axis” underscores the impact of gut microbes and their metabolites on health and disease, with dysbiosis serving as a triggering event in several diseases, including CKD. This review provides a comprehensive overview, focusing on the gut–liver axis, and explores well-established bioactive substances as well as specific, less-known nutraceuticals showing promise in supporting kidney health and positively influencing CKD progression.